Tożsamość estetyczna a dyskurs rozmycia kulturowego - Jansen, Joel (Er(r)go. Teoria - Literatura - Kultura, 2010)
Joel Jansen Aesthetic Identity and the Discourse of Cultural Greyout Taking as a departure point the case of illegal mass-reproduction of an image painted by an Australian Aboriginal artist, Joel Jensen explores the relationship between culture, art and identity. He points to the threat referred to as "cultural greyout," i.e. the inability to reproduce the identities of the past due to the contemporary mass-production of artefacts in which those identities are reflected. Jensen follows Arthur Danto's view that mass reproduction changes the conveyed meaning of an artwork and, by being distributed as a commodity within the dominating society, poses a threat to the identity of the community in which the artefact was created since the history of an artwork, i.e. the circumstances that determine the artwork's creation and distribution, contribute to its aesthetic characteristics. These, in turn, remain formative for the construction of the community's identity.